Strain states in GaN films grown on Si(111) and Si(110) substrates using a thin AlN/GaN superlattice interlayer. Issue 3 (19th March 2014) - Shen, X. Q.; Takahashi, T.; Ide, T.; Shimizu, M.
Abstract: We report the characterization results of the strain states in GaN films grown both on Si(111) and Si(110) substrates by applying a thin AlN/GaN superlattice structure (SLs) as an interlayer (IL). The strain states in the GaN films grown on Si(111) and Si(110) substrates are compared. It is demonstrated that the modulation effect by the SL ILs on the strain state in the GaN film is universal although different behaviours on the Si(111) and Si(110) substrate are observed due to the different lattice symmetry relationship between the substrate and the epilayer. By using the technique, we succeeded in growing thick continuous GaN films (> 3 µm), which are necessary for the high‐power, high‐voltage device applications. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)